2014
DOI: 10.1177/0273475313520443
|View full text |Cite
|
Sign up to set email alerts
|

A Parsimonious Instrument for Predicting Students’ Intent to Pursue a Sales Career

Abstract: Students' desire and intention to pursue a career in sales continue to lag behind industry demand for sales professionals. This article develops and validates a reliable and parsimonious scale for measuring and predicting student intention to pursue a selling career. The instrument advances previous scales in three ways. The instrument is generalizable across academic settings and is shown to be sensitive to differences across varied course coverage and learning activities. The instrument is parsimonious and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
122
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(132 citation statements)
references
References 44 publications
6
122
2
2
Order By: Relevance
“…The original authors (Peltier et al, 2014) reported factor loadings of .72-.83 for this measure, with a reliability coefficient of .89. The results provide additional evidence of the factor structure and dimension reliability, with factor loadings of .68-.84 and an alpha coefficient of .90.…”
Section: Quantitative Measures and Hypothesismentioning
confidence: 97%
See 3 more Smart Citations
“…The original authors (Peltier et al, 2014) reported factor loadings of .72-.83 for this measure, with a reliability coefficient of .89. The results provide additional evidence of the factor structure and dimension reliability, with factor loadings of .68-.84 and an alpha coefficient of .90.…”
Section: Quantitative Measures and Hypothesismentioning
confidence: 97%
“…One dimension of the Intent to Pursue a Sales Career (ITPSC) Scale (Peltier, Cummins, Pomirleanu, Cross, & Simon, 2014) was used to assess potential changes in students' perceptions as a result of the experiential learning project: sales knowledge. This dimension was chosen because it facilitates a self-report assessment of the students' development of selling skills.…”
Section: Quantitative Measures and Hypothesismentioning
confidence: 99%
See 2 more Smart Citations
“…Feelings about a profession include feelings that the profession is interesting, has a sense of accomplishment, good and worthwhile and providing a kind of emotional and financial security (Karakaya et al, 2011;Peltier, Cummins, Pomirleanu, Cross, & Simon, 2014;Wessels & Steenkamp, 2009). Negative feelings for the accounting profession can be formed throughout life and can affect interest for the profession.…”
Section: General Feelings About Accounting Professionmentioning
confidence: 99%